A Study of Under-Graduate Studentsâ Attitude towards Computer - Hasan, Mohd; Parvez, Mohammad (EDUCARE, 2015)
ABSTRACT: Nowadays, the role of Information and Communication Technology (ICT), especially in education sector, has been increased to empower the educational activities. Computer as an integrated part of ICT has become a very crucial and handy tool to perform the various required educational activities. All the ladders of education system have their own ways and purpose to use the computer based applications in their set up. So, computer education has become mandatory in every walks of the life. Educational activities at any level cannot be performed effectively until and unless one seeks help from the computer based applications. For an effective use of computer, one should have proper attitude towards computer as well as computer education. That is why the present study aims to investigate the computer attitude of under-graduate students of Science and Social Science streams. A sample of 100 (male = 50, female = 50) was drawn by using standardized Computer Attitude Scale, according to T. Khatoon & M. Sharma (2011), from the under-graduate students of Science and Social Science Faculties of AMU (Aligarh Muslim University) in Aligarh UP (Uttar Pradesh), India. A non-probable purposive sampling technique was used to draw the sample. In order to test the hypotheses, descriptive statistical measures like Mean and Standard Deviation and t-test were applied. Analysis of data revealed that there is no significant difference between the computer attitude of under-graduate students of Sciences and Social Science streams at all the basis of comparison. The study has an educational implication for educational practitioners and professionals.KEY WORDS: Information and communication technology, computer education, computer attitude, gender, science and social science streams, and educational practitioners and professionals.Â Â About the Authors: Mohd Hasan is a Research Scholar at the Department of Education AMU (Aligarh Muslim University), Aligarh, Uttar Pradesh, India; and Assoc. Prof. Dr. Mohammad Parvez is a Lecturer at the Department of Education AMU, Aligarh, Uttar Pradesh, India. For academic purposes, the author can be contacted via mobile phone at: +91-9451513343 or be searched at an e-mail: mhasanedu@gmail.comHow to cite this article? Hasan, Mohd & Mohammad Parvez. (2015). âA Study of Under-Graduate Studentsâ Attitude towards Computerâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.23-30. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (May 13, 2015); Revised (July 16, 2015); and Published (August 25, 2015).